Risk Potency of Lead Exposure to Decrease Cognitive Ability of Productive Age Community in Indonesia Emas 2045 - Rika Wijiyanti (Fakultas Matematika dan Ilmu Pengetahuan Alam, 2023)
Lead (Pb) can decrease children’s IQ and cognitive abilities. This study aims to analyze the risk characteristics of lead exposure in children aged 4-5 years related to the risk of low IQ as an obstacle in realizing “Indonesia Emas” of 2045 and to analyze the role of medical intelligence to anticipate these potential risks. This study was conducted in Tangerang Industrial Area. The Pb concentrations in food, urine, water, and rice were tested using Flame Atomic Absorption Spectrometry (FAAS). The results showed that Pb levels in food were lower than the Limit of Quantification (LOQ) method, thus, censored data rule was used for data processing. Overall results indicate a risk of causing long term cognitive impairment. However, The results of the calculation of exposure and Margin of Exposure (MOE) are based on the assumption of 50% and 100% of LOQ value. The obtained exposure and MOE values can not be used to said that the status of Pb exposure occurs. The resulting data is still useful as a basis for further research.